Anticancer and Cytotoxic Evaluation of Padikara Parpam Combined with L-Ascorbic Acid (PPLAA) - A. Anitha; V. Arvind; K. Revathi; E. Logeswari; Archana V (The Bioscan, 2025)
Cancer is still one of the leading causes of death globally a lot of research is being done to develop safer, more effective anticancer drugs that come from natural sources. Because of their mineral and botanical components, traditional Siddha medicines have demonstrated exceptional medicinal potential. The present study analyzes the in vitro anticancer and cytotoxic characteristics of Padikara Parpam coupled with L-Ascorbic Acid (PPLAA) against MCF-7 (human breast cancer) and VERO (normal kidney epithelial) cell lines utilizing the MTT assay. The findings showed that PPLAA significantly inhibited the growth of MCF-7 cancer cells in a dose-dependent manner, with the lowest cell viability (3.4%) occurring at the highest concentration (500 μg/mL). On the other hand, VERO cells showed negligible cytotoxicity (7.0% drop in cell viability at 500 μg/mL), suggesting a good therapeutic selectivity. The findings suggest that PPLAA could serve as a potential natural anticancer agent with limited toxicity toward normal cells.